Recurrent Focal Segmental Glomerulosclerosis in Renal Allograft Recipients: Role of Human Leukocyte Antigen Mismatching and Other Clinical Variables. (15th June 2011) - Sharief, Shimi; Mahesh, Shefali; Del Rio, Marcela; Telis, Vivian; Woroniecki, Robert P.
Abstract : Recurrence of focal segmental glomerulosclerosis (FSGS) after renal transplantation impacts long-term graft survival and limits access to transplantation. We hypothesized that HLA donor/recipient matching could be used as a surrogate marker of recurrence. In a retrospective study of 42 pediatric and 77 adult subjects with primary FSGS, transplanted from 1990 to 2007 at a single center, we analyzed the degree of donor/recipient HLA compatibility and other clinical variables associated with FSGS recurrence. There were total of 131 allografts for primary FSGS (11 subjects were transplanted twice, and 1 had a third allograft) with 20 cases of FSGS recurrence (17 children) in the primary allograft, and two children who had FSGS recurrence in the second allograft. Fifty-two subjects (40%) were African American, and 66 (50%) Caucasians. Recurrent FSGS and controls were not different for age at transplant, gender, donor source, acute/chronic rejection episodes, and HLA matches. Recurrent FSGS was not associated with HLA mismatches; power equals 83%. Immunosuppressive regimen had no effect on recurrence of FSGS, P = .75 . Recurrent FSGS is not associated with HLA mismatching, acute cellular or vascular rejection, and occurs primarily in the pediatric population.